(untitled) (Fiep Bulletin - online, 2011)
Health professionals who work in service pre-hospital care (PHC) emergency faced, daily stressful situations, once they develop their practice in borderline levels of life. We therefore believe that the systematic survey of publications dealing with the PHC, is very important for professionals to be instrumentalized in order to know the national and international reality. This study aimed to characterize the scientific production on the PHC, published in LILACS (BIREME), as the database, study type, publication type, method, form of publication and thematic of publication. This is a literature review, exploratory, descriptive research with prospective data and quantitative approach, held in LILACS. Data collection was performed during the months of march and april 2009. In this, we found a total of 10 work. Most of the scientific research used the descriptive study, literature review and transverse (30% each), with a quantitative approach (60%), published as articles (100%) and available in full text (70%). As the theme, these were about the characterization of lesions (40%) and profile of the victims (30%). With these results, we intend to contribute to the improvement of professionals working or wishing to further his studies of the PHC. It is therefore the priority to continue to conduct research on these issues and at the same time invest in the development of research directed to theoretical and practical aspects of the PHC, contributing to a better preparation of health professionals who work in area.